Percutaneous nephroscopy versus flexible ureteroscopy in the treatment of calyceal diverticulum calculi: a meta-analysis - Conglei Hu; Rui Ma; Yongxiang Shao; Zilong Liang; Meng Cheng; Haofeng Pang; Liping Yao; Fei Liu (BMC Urology)
Abstract Background There is still controversy about the best minimally invasive surgical method for the treatment of calyceal diverticulum calculi. We conducted meta-analysis to evaluate the effectiveness and safety of PCNL and FURL in the treatment of calyceal diverticulum calculi. Methods We searched Pubmed, Cochrane Library, Web of Science, Embase, Clinical trial platform, CNKI, VIP until April 2024. We utilized the Newcastle–Ottawa Scale (NOS, 0 to 9 stars) to assess the quality of the included literature. Results Totally 15 high-quality studies with 755 patients were included in the meta-analysis. Meta-analysis showed that FURL group was better than PCNL group in blood loss [SMD = 1.713, 95%CI:(0.858, 2.568), Z = 3.928, P = 0.000] and hospital stay [SMD = 2.611, 95%CI: (1.726, 3.496), Z = 5.784, P = 0.000], there was no significant difference in operating time [SMD = 0.079, 95%CI:(-0.43, 0.589), Z = 0.306, P = 0.760], complication rate [OR = 1.793,95%CI: (0.952,2.602), Z = 1.586, P = 0.113], stone-free rate [OR = 1.339, 95%CI: (0.576, 3.112), Z = 0.678, P = 0.497] and symptom-free rate [OR = 3.826,95%CI: (0.561,10.238), Z = 0.966, P = 0.334] as well. Conclusion Whether FURL is indeed superior to PCNL in safety, whether FURL's efficacy is really close to PCNL, and whether FURL can surpass PCNL as the first choice for the treatment of renal diverticulum stones in the future need to be further verified by multi-center, large-sample and high-quality studies.